Girl's guide to DIY fashion : design & sew 5 complete outfits : mood boards, fashion sketching, choosing fabric, adding style - Low, Rachel, 1972- (FunStitch Studio,an imprint of C&T Publishing, 2015)
"Give your resident young designer all the tools she needs to create five cute outfits that will take her from home to school to hanging out and back again. From the owner of the NYC sewing studio Pins & Needles comes the definitive guide to mood boards, fashion design, and sewing for girls."--Provided by publisher.